2016
DOI: 10.1038/srep37186
|View full text |Cite
|
Sign up to set email alerts
|

A simple design for microwave assisted digestion vessel with low reagent consumption suitable for food and environmental samples

Abstract: The objective of this work is to prepare a cost-effective, low reagent consumption and high performance polytetrafluoroethylene (PTFE) vessel that is capable to work in domestic microwave for digesting food and environmental samples. The designed vessel has a relatively thicker wall compared to that of commercial vessels. In this design, eight vessels are placed in an acrylonitrile butadiene styrene (ABS) holder to keep them safe and stable. This vessel needs only 2.0 mL of HNO3 and 1.0 mL H2O2 to digest 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…The values for Cu and Zn did not show any significant differences from certified concentrations as both p-values, which were obtained from one-sample t-test, were more than 0.05. In a report by Gholami, Behkami, Zain and Bakirdere (2016), it was stated that the values obtained for Cd, Cu, and Zn were 0.0219 ± 0.0012 µg/g, 2.34 ± 0.09 µg/g and 18.72 ± 0.51 µg/g respectively for NIST 1568b Rice Flour. The values obtained in this study were in good agreement with the certified values and those reported in Gholami et al (2016).…”
Section: Results and Discussion Analytical Quality Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…The values for Cu and Zn did not show any significant differences from certified concentrations as both p-values, which were obtained from one-sample t-test, were more than 0.05. In a report by Gholami, Behkami, Zain and Bakirdere (2016), it was stated that the values obtained for Cd, Cu, and Zn were 0.0219 ± 0.0012 µg/g, 2.34 ± 0.09 µg/g and 18.72 ± 0.51 µg/g respectively for NIST 1568b Rice Flour. The values obtained in this study were in good agreement with the certified values and those reported in Gholami et al (2016).…”
Section: Results and Discussion Analytical Quality Controlmentioning
confidence: 98%
“…In a report by Gholami, Behkami, Zain and Bakirdere (2016), it was stated that the values obtained for Cd, Cu, and Zn were 0.0219 ± 0.0012 µg/g, 2.34 ± 0.09 µg/g and 18.72 ± 0.51 µg/g respectively for NIST 1568b Rice Flour. The values obtained in this study were in good agreement with the certified values and those reported in Gholami et al (2016). Thus, results obtained are acceptable for further discussions.…”
Section: Results and Discussion Analytical Quality Controlmentioning
confidence: 98%
“…However, this technique requires sample preparation steps before multi-elemental analysis in complex matrices [10]. Thus, solid samples like coal should be completely dissolved and digested prior to elemental analysis [11]. Usually, sample preparation is performed by a conventional hotplate or microwave-assisted digestion [12].…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, se encuentran disponibles varias metodologías normalizadas, de distinta complejidad y límites de detección, para la determinación de la concentración de As en diferentes matrices, tales como los métodos por espectrofotometría UV-Vis, espectrometría de masas, espectrometría de emisión y la espectrofotometría de absorción atómica (Association American Public Health et al, 2000;M.I. Litter et al, 2009;Vieira et al, 2005;Zagal & Sadzawka, 2007) sin embargo, algunos pueden conllevar pérdida del analito, mientras que otros, más exactos y precisos, deben ser ajustados según las condiciones de cada laboratorio de ensayo, de tal manera a lograr la optimización y emisión de resultados confiables (García-Rico & Jara-Marini, 1996;Gholami et al, 2016).…”
unclassified
“…La técnica de digestión por microondas se caracteriza por su rapidez, eficiencia, reproducibilidad y reducción de uso de reactivos y muestras (Gholami et al, 2016) y puede ser utilizada para una diversidad de matrices como alimentos, fluidos biológicos, muestras ambientales entre otros (García-Rico & Jara-Marini, 1996;Gholami et al, 2016;Nazzal et al, 2021;Vieira et al, 2005). Otra ventaja de este método es que se obtienen muestras digeridas en su totalidad que pueden ser leídas por el Espectrofotómetro de Absorción Atómica (EAA), caracterizado por su elevada sensibilidad y robustez, tal es así que para la cuantificación de arsénico, cuando el EAA se acopla al Generador de Hidruro (GH), la concentración de arsénico puede llegar al límite de detección de 1,45 ng.mL -1 y al límite de cuantificación de 2,53 ng.mL -1 .…”
unclassified